Polyacrylamide-Sodium Alginate Hydrogel Releasing Oxygen and Vitamin C Promotes Bone Regeneration in Rat Skull Defects - Zhao, Bin; He, Jingya; Wang, Feng; Xing, Ruxiao; Sun, Bin; Zhou, Yanmin (Frontiers in Materials, 2021)
Oxygen is essential for cell survival and tissue regeneration. Scaffolds releasing oxygen have been hypothesized as an ideal strategy for bone repair. However, excessive oxygen supply will disturb the redox balance, lead to oxidative stress, and affect bone regeneration. In this study, we synthesized a hydrogel from sodium alginate and loaded it calcium peroxide nanoparticles as an oxygen generating material and vitamin C as a pH regulator and antioxidant. The composite hydrogel, with a pH value close to physiological humoral fluid, could release oxygen to alleviate hypoxia in the bone defect and reduce the side effects of excessive hydrogen peroxide. In in-vitro experiments, the composite hydrogel promoted the osteogenic differentiation and ALP and mineralization ability of rat bone marrow mesenchymal stem cells in a hypoxic environment (2 % O2). In animal experiments, the composite hydrogel was applied in rat skull defect models. It promoted the healing of bone defects. These results suggest that sodium alginate hydrogel releasing oxygen and vitamin C is suitable for cell survival and tissue regeneration in a hypoxic environment and has good application prospects in bone defect repair.